Halal Travel Decision Analysis (Case Study: Visitors to Pilgrimage Tourism at Pringsewu District) - Ayu Wulandari; Heri Junaidi; Maftukhasholikhah (Institut Agama Islam (IAI) Al-Qolam, 2023)
Traveling is an activity that is done to unwind and get entertainment. Usually, tourist attractions have inherent value or culture, natural beauty and history. The example is pilgrimage tourism in the Pringsewu district which has a historical value from scholars in Lampung. This study uses a quantitative approach with the aims to examine the effect of promotion and innovation on halal travel decisions from 2016-2022. The measurement this study using SPSS statistical tools, secondary data using questionnaires and documents contained in BPS Lampung 2016-2022. Researchers came to the conclusion that (1) the promotion variable has a positive effect on halal travel decisions to visit pilgrimage tourism. (2) innovation variables have a positive effect on halal travel decisions on pilgrimage tourism visitors in Lampung Pringseweu district.